A Case Study On The Impact Of The Credit Guarantee Scheme On Small And Medium-Sized Entreprises In Penang And Kedah - Mohd Khairuddin, Hashim (1995)
The credit guarantee programs initiated by the Malaysian Government are directed toward assisting small and medium-sized enterprises (SMEs) which lack internal financing. The Credit Guarantee Corporation’s Principal Guarantee Scheme (PGS) was introduced on April 3,1989 to enable SMEs to obtain external financing which would not have been available without the PGS. This case study examined the impact of the PGS on SMEs in Penang and Kedah. In determining the effectiveness of the PGS, the study focused on the following: a. response to the PGS since its inception; b. extent of participation by the banks in channelling the funds; and c. performance of SMEs after receiving the PGS facilities. Further, the findings indicated that the impact of the PGS was not entirely favourable on SMEs, that is, the objectives were not met. Finally, this study suggests eight recommendations which will strengthen the position of the PGS, as well as, increase the efforts and support for the SME sector.